Financiamento da saúde: proposta e avaliação de modelo estimativo do custeio global de hospitais públicos - Márcia Mascarenhas Alemão (2017)
Health, understood here as the Unified Health System (SUS), is one of the pillars of the social protection network instituted by the Federal Constitution of 1988. Its sustainability, permanent concern in the most diverse segments of Brazilian society, is, however, a major challenge for SUS management. In the scenario of discussion about SUS financing, the remuneration of hospitals represents a broad field of academic study. Objective The objective of this research is to propose a global estimation model for the costing of hospital establishments that subsidizes the discussion about the remuneration of hospital services to the SUS, adopting the knowledge base of costs of Fundação Hospitalar do Estado de Minas Gerais (FHEMIG). Methodology Taking the Contingency Theory and Fundamental Analysis, this research in heath financing uses the triangulation method to understand the researched institutional reality; the @Risk software, to simulate global hospital costing; and to the Focus Group or Panel of Experts, to deepen the understanding of the proposed model. Results of the research The Fundamental Analysis and Contingency Theory allowed the identification of the constructs of the hospital modules as criteria of representation of the hospital services provided to the SUS. To simulate the global hospital cost, the survey used FHEMIG's cost-knowledge base. An adjustment equation was added as a refinement to the model. It was composed of variables capable of particularizing hospitals and whose weighting allowed the further refinement of the minimum and maximum values generated by the model. The Equation of Adjustment "points" to the percentile of the simulation for the adjustment of the global costing to more specific hospitals. Conclusion Based on cost information processed according to this researchs methodology, the global hospital estimation model allows the discussion of health financing, generating evidence in the reduction of asymmetries, distortions and uncertainties in the evaluation of the resources needed to maintain the financial economic balance of the hospitals. It thus makes possible fairer and more realistic remuneration policies for hospitals providing SUS services.